Cadmium coordination polymer for regulating and controlling photostimulation response behavior through thermal phase change as well as preparation method and application of cadmium coordination polymer
By performing thermal phase change treatment on the cadmium coordination polymer, it can undergo [2+2] halo addition reaction under 365nm ultraviolet light irradiation, solving the problem that existing cadmium coordination polymers cannot achieve photo stimulation response behaviors. , realizes the photoresponse effect of photodrive materials.
Patent Information
- Application Number
- CN202411524421.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
The existing cadmium coordination polymer cannot undergo [2+2] halo addition reaction under 365nm ultraviolet light, and cannot achieve photostimulation response behavior.
By heating the cadmium coordination polymer to a certain temperature, it undergoes a thermal phase change, removes the coordination water molecules and rearranges the C=C bonds, so that it meets the solid [2+2] cycloaddition conditions, thereby irradiating at 365nm ultraviolet light The cycloaddition reaction occurs under the condition, resulting in photostimulus response behavior.
The photostimulation response behavior is regulated through thermal phase change, so that the cadmium-coordinated polymer can undergo [2+2] aura addition reaction under ultraviolet light irradiation, resulting in mechanical deformation and photoresponse behavior, and has wide application prospects.
Smart Images

Figure CN119409981A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of light stimulus response materials, and in particular relates to a cadmium coordination polymer capable of regulating light stimulus response behavior through thermal phase change, and a preparation method and application thereof. Background Art
[0002] Intelligence is a key strategic area for the development of devices and new materials today, and has become a hot frontier in international scientific development today. Coordination polymers (CP) are a new type of crystalline material formed by self-assembly of metal ions and organic bridging ligands through coordination bonds. Photoresponsive molecular fragments can be embedded in a highly ordered and specially arranged coordination polymer skeleton. Under light radiation, the photosensitive molecules undergo chemical reactions to generate photoinduced stress, thereby driving the material to undergo mechanical deformation. Intelligent light-driven materials represented by coordination polymers can produce different degrees of PS behavior in response to external light stimulation to reflect their driving ability. At present, the photoresponsive behavior of light-induced reactions such as azobenzene isomerization, reversible cyclization, and [4+4] anthracene dimerization has been studied. In contrast, the [2+2] cycloaddition reaction has the advantages of rapid reaction, mild reaction conditions, predictability and controllability.
[0003] Photochemical [2+2] cycloaddition of styrenes provides a common route for the synthesis of polysubstituted cyclobutanes. The construction of aryl-substituted cyclobutane rings is a prominent structural feature of a large number of biologically active molecules and is crucial for the synthesis of natural products and drug discovery. The [2+2] photocycloaddition reaction can be said to be the most direct method for the preparation of cyclobutane-containing compounds, which mainly relies on the activation of styrenes by electron or energy transfer from transition metals or organic photosensitizers. However, due to the disordered arrangement of reactive olefin molecules in solution, the [2+2] cycloaddition is difficult. According to Schmidt's criterion, when the C=C bonds are parallel and the distance between the olefin groups is ≤ When , the solid-state [2+2] photodimerization of olefins can occur. The templated solid-state [2+2] photodimerization of olefins makes the reaction more reliable.
[0004] Coordination polymers sometimes fail to play a role in the photodimerization of template olefins due to inappropriate arrangement of C=C groups. However, external stimuli such as heat, light, and pressure can cause the C=C groups to rearrange in situ, allowing the photodimerization reaction to proceed smoothly. After searching, there are currently few reports on coordination polymers that cannot undergo [2+2] photocycloaddition reactions themselves, but can achieve the regulation of their photostimulation response behavior through thermal phase transition. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a cadmium coordination polymer whose light-stimulated response behavior is regulated by thermal phase change, and a preparation method and application thereof. The cadmium coordination polymer itself cannot undergo a [2+2] photocycloaddition reaction under 365nm ultraviolet light irradiation (showing apparent inertness), but it produces an obvious thermal phase change after being heated to a certain temperature. At this time, it can induce a [2+2] photocycloaddition reaction under 365nm ultraviolet light irradiation to produce light-stimulated response behavior.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A cadmium coordination polymer with a molecular formula of C 118 H 114 Cd3 12 N6O 15 , belongs to the monoclinic system, P21 / c space group, unit cell parameters are: a= α=90.00°, β=114.694(8)°, γ=90.00°.
[0008] The preparation method of the cadmium coordination polymer of the present invention is as follows: a ligand represented by the following formula (I), cadmium sulfate and 2,6-dichlorobenzoic acid are placed in a reaction container, a mixed solvent is added, the system is adjusted to be acidic, the reaction container is sealed and then placed under heating conditions for reaction, and the cadmium coordination polymer is obtained; wherein the mixed solvent is a composition composed of N,N-dimethylacetamide and water in a volume ratio of 1:6.5-7.0;
[0009]
[0010] The applicant discovered through experiments that the composition and ratio of the mixed solvent are crucial to whether the cadmium coordination polymer can be prepared. When the volumes of N,N-dimethylacetamide and water are not within the above-mentioned limited range, no crystals are precipitated after the reaction is completed and then naturally cooled; in addition, under the same other conditions, when N,N-dimethylformamide, N,N-diethylformamide or 1,4-dioxane with similar polarity are used instead of N,N-dimethylacetamide, no crystals are precipitated after the reaction is completed and then naturally cooled.
[0011] In the above preparation method, the cadmium sulfate can be one or a combination of two or more selected from anhydrous cadmium sulfate, cadmium sulfate hydrate and cadmium sulfate 8 / 3 hydrate, preferably cadmium sulfate 8 / 3 hydrate.
[0012] In the above preparation method, it is further preferred that the volume ratio of N,N-dimethylacetamide to water is 1:6.6-6.8. The system can be adjusted to acidity with an inorganic acid or an organic acid such as nitric acid or hydrochloric acid, preferably the pH of the system is adjusted to ≤5.0, and more preferably the pH of the system is adjusted to 3.0-4.0. The reaction is preferably carried out at ≥100°C, more preferably 135-150°C. When the reaction is carried out at 135-150°C, the reaction time is preferably controlled to be 8-12h.
[0013] In the above preparation method, the ratio of the ligand represented by formula (I), cadmium sulfate and 2,6-dichlorobenzoic acid is usually a stoichiometric ratio, and the amount of the mixed solvent used is preferably sufficient to dissolve all the raw materials participating in the reaction. Preferably, the amount is calculated based on the basis of adding 0.3 to 5 mL of the mixed solvent to 1 mg of the ligand represented by formula (I).
[0014] In the above preparation method, the ligand shown in formula (I) is (E)-4-(4-(phenylethynyl)phenylvinyl)pyridine, which is prepared by Heck reaction of 1-bromo-4-(phenylethynyl)benzene and 4-vinylpyridine, wherein the 1-bromo-4-(phenylethynyl)benzene involved can be prepared by referring to the existing literature (Khlobystov, AN; Brett, MT; Blake, AJ; Champness, NR; Gill, PM; O'Neill, DP; Teat, SJ; Wilson, C.; Schroder, M., Stereoselective association of binuclear metallacycles in coordination polymers. Journal of the American Chemical Society 2003, 125 (22), 6753-61.), or can be synthesized by self-designed route. In the present application, the ligand shown in formula (I) is preferably prepared by the following method:
[0015] 1) 1-bromo-4-iodobenzene, 4-alkynylpyridine, an organic solvent and a weak base are placed in a reaction vessel, a palladium catalyst and a monovalent copper catalyst are added, and an iodine substitution reaction is carried out under an atmosphere protection condition, and the solid is collected and dried to obtain an intermediate product (1-bromo-4-(phenylethynyl)benzene);
[0016] 2) The intermediate product, 4-vinylpyridine, an organic solvent, a palladium catalyst and a weak base are placed in a reaction vessel, and a Heck reaction is carried out under an atmosphere protection condition. After the reaction is completed, the mixture is cooled to room temperature, washed with water, filtered, and the solid is collected and dried to obtain the ligand ((E)-4-(4-(phenylethynyl)phenylvinyl)pyridine).
[0017] In the preparation method of the above ligand, the organic solvent can be tetrahydrofuran, N,N-dimethylformamide or 1,4-dioxane; the weak base can be one or a combination of triethylamine, diethylamine, sodium carbonate, potassium carbonate or cesium carbonate, and its dosage is usually 3 to 5 times the weight of 1-bromo-4-iodobenzene or the intermediate product. For palladium catalyst and monovalent copper catalyst, their selection and dosage are conventional selections in the prior art, wherein the palladium catalyst is preferably tetrakis(triphenylphosphine)palladium and / or bistriphenylphosphine palladium dichloride, and its dosage is preferably 0.2 to 0.6 times the weight of 1-bromo-4-iodobenzene or the intermediate product. For monovalent copper catalyst, monovalent copper halide, such as cuprous iodide, cuprous chloride or cuprous bromide, is usually selected, and its dosage is preferably 0.1 to 0.2 times the weight of 1-bromo-4-iodobenzene. When the iodine substitution reaction is usually carried out at 20 to 40°C, the reaction time is preferably controlled at 8 to 12 hours. When the Heck reaction is usually carried out at 110-130°C, the reaction time is preferably controlled within 60-84 hours.
[0018] The crude product of the ligand prepared by the above method can be further purified by silica gel column chromatography. The eluting solvent used in the chromatography is a composition composed of n-hexane and dichloromethane, wherein the volume ratio of n-hexane to dichloromethane is preferably 2-5:1.
[0019] The present invention also provides a composite film, comprising the crystals of the cadmium coordination polymer after being heated to above 150° C. to undergo thermal phase change. The thickness of the composite film is determined according to needs and can be 25 to 150 μm.
[0020] The preparation method of the composite film is as follows: the crystals of the cadmium coordination polymer are heated to above 150°C to undergo phase change, and then ground and mixed evenly with the substrate, and the resulting viscous liquid is poured into a mold, dried, and peeled off. The substrate can be one selected from PVA (polyvinyl alcohol), chitosan, polyvinylidene fluoride and polypropylene, preferably a 5-15wt% PVA aqueous solution; more preferably a 10wt% PVA aqueous solution. The mass ratio of the cadmium coordination polymer to the PVA aqueous solution can be 1-3:10.
[0021] The applicant found in the experiment that the cadmium coordination polymer of the present invention will remove the coordinated water molecules after being heated to 150°C and kept warm for more than 2 hours, causing the structure of the coordination polymer to change. At this time, irradiation with 365nm ultraviolet light can cause a [2+2] photocycloaddition reaction, resulting in light stimulus response behavior. The insulation time is usually 2 to 12 hours, and it is more preferred to heat to 165 to 180°C and keep warm for 3 to 6 hours to cause the cadmium coordination polymer to undergo a phase change. Whether the cadmium coordination polymer undergoes a thermal phase change can be found by the XRD diagram before and after heating. After the phase change occurs due to heating, the XRD peak changes.
[0022] The invention also provides a photo-driven actuator, which is made from the composite film.
[0023] Specifically, the composite film can be made into the photoactuator by cutting and fixing the composite film.
[0024] Based on the above findings, the present invention further includes the use of the above cadmium coordination polymer or composite film in photo-driven driving.
[0025] Compared with the prior art, the present invention is characterized in that:
[0026] 1. The present invention provides a novel cadmium coordination polymer that regulates light stimulus response behavior through thermal phase transition, wherein the C=C bonds of the cadmium coordination polymer are not arranged in parallel, and the distance between the olefin bond centers is greater than It does not meet the Schmidt criterion for solid [2+2] cycloaddition, so it cannot undergo a [2+2] photocycloaddition reaction under 365nm ultraviolet light. The applicant heats the cadmium coordination polymer to remove the coordinating solvent water molecules to cause structural changes, and the C=C bonds are rearranged to meet the solid [2+2] cycloaddition conditions, so that a cycloaddition reaction can occur under 365nm ultraviolet light to produce light-stimulated responsive behavior. In view of the characteristics of the cadmium coordination polymer described in the present invention that its light-stimulated responsive behavior is regulated by thermal phase change, it can be applied to some special applications, such as optical brakes, soft robots, optical equipment and other fields, and has good application prospects.
[0027] 2. The design of the present invention provides a solution for coordination polymers that cannot produce light-stimulated responsive behavior by themselves, and uses thermal phase change to achieve the regulation of light-stimulated responsive behavior, providing a new synthetic idea and approach for the design and preparation of light-responsive crystals.
[0028] 3. The cadmium coordination polymer of the present invention is prepared by solvent thermal reaction of ligand (E)-4-(4-(phenylethynyl)phenylvinyl)pyridine, cadmium sulfate and 2,6-dichlorobenzoic acid, and the preparation method is simple, the reaction conditions are mild, and the photoconversion efficiency is high. The chemical properties of the target product are stable, the reagents used are relatively common and less polluting, and it is safe and reliable. The intermediate ligands involved in the preparation process are stable, and harsh reaction conditions and storage conditions are not required. The operation is simple and does not require complicated treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The nuclear magnetic resonance hydrogen spectrum and carbon spectrum of the intermediate product prepared in Example 1 of the present invention; wherein (a) is the hydrogen spectrum, and (b) is the carbon spectrum.
[0030] Figure 2The nuclear magnetic resonance hydrogen spectrum and carbon spectrum of the ligand prepared in Example 1 of the present invention; wherein (a) is the hydrogen spectrum, and (b) is the carbon spectrum.
[0031] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of the coordination polymer CP1 prepared in Example 1 of the present invention.
[0032] Figure 4 It is a structural diagram of the coordination polymer CP1 crystal prepared in Example 1 of the present invention; wherein (a) is the structural diagram of the coordination polymer CP1 crystal (hydrogen atoms omitted), and (b) is the coordination structure diagram of the metal ions in the coordination polymer CP1 crystal (including hydrogen atoms).
[0033] Figure 5 This is a mass spectrum fitting diagram of a single crystal sample of the coordination polymer CP1 prepared in Example 1 of the present invention and a single crystal simulation.
[0034] Figure 6 This is the thermogravimetric analysis diagram of the coordination polymer CP1 prepared in Example 1 of the present invention.
[0035] Figure 7 XRD spectra of the coordination polymer CP1 prepared in Example 1 of the present invention at phase transitions of 298K and 443K.
[0036] Figure 8 This is the infrared spectra of the coordination polymer CP1 prepared in Example 1 of the present invention at 298K and 443K.
[0037] Fig. 9 These are crystal pictures of the coordination polymer CP1 prepared in Example 1 of the present invention irradiated with 365nm ultraviolet light at 298K and 443K.
[0038] Fig.10 These are hydrogen nuclear magnetic resonance spectra of the coordination polymer CP1 prepared in Example 1 of the present invention under 365nm ultraviolet light irradiation at temperatures of 298K and 443K respectively.
[0039] Fig.11 This is a diagram of the light stimulus response behavior of the coordination polymer CP1 prepared in Example 1 of the present invention after thermal phase transition under 365nm ultraviolet light irradiation.
[0040] Fig.12 This is a diagram showing the light response of the composite film holding up the small ball in Application Example 2.
[0041] Fig.13 This is a diagram showing the light response of the composite film in Example 3 to simulate the spread of a bird's wings.
[0042] Fig.14 This is a diagram showing the light response of the composite film in Example 4 to simulate an arch bridge. DETAILED DESCRIPTION
[0043] In order to better explain the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments, but the embodiments of the present invention are not limited thereto.
[0044] Example 1
[0045] 1) Preparation of the intermediate product 1-bromo-4-(phenylethynyl)benzene: 3 g of 1-bromo-4-iodobenzene, 1.3 g of 4-alkynylpyridine, 0.77 g of bistriphenylphosphine palladium dichloride and 0.21 g of cuprous iodide were added to a 250 mL eggplant-shaped reaction bottle, and then 20 mL of tetrahydrofuran and 5 mL of triethylamine were added, nitrogen was introduced, and the reaction was carried out at room temperature for 12 h. After the reaction was completed, the mixture was washed with water and filtered, and the solid was collected and dried to obtain a light yellow powder; the obtained powder was characterized by H NMR and C NMR (the spectrum is shown in FIG. Figure 1 As shown), it was determined to be the intermediate product 1-bromo-4-(phenylethynyl)benzene;
[0046] 2) Preparation of ligand (E)-4-(4-(phenylethynyl)phenylvinyl)pyridine: 3 g of 1-bromo-4-(phenylethynyl)benzene, 1.48 g of 4-vinylpyridine, 1.94 g of bistriphenylphosphine palladium dichloride and 0.25 g of potassium carbonate were added to a 250 mL eggplant-shaped reaction bottle, and then 20 mL of N,N-dimethylformamide was added, nitrogen was introduced, and the reaction was stirred in an oil bath at 120° C. for 72 h. After the reaction was completed, the mixture was cooled to room temperature, washed with water, filtered, and the solid was collected and dried to obtain a crude ligand product; the crude product was purified by silica gel column chromatography (n-hexane / dichloromethane=3 / 1, v / v) to obtain an orange powder; the powder was characterized by H NMR and C NMR (the spectrum is shown in FIG. 2 ). Figure 2 As shown), the ligand was determined to be (E)-4-(4-(phenylethynyl)phenylvinyl)pyridine;
[0047] 3) Preparation of cadmium coordination polymer: 6.5 mg of ligand (E)-4-(4-(phenylethynyl)phenylvinyl)pyridine, 9.5 mg of 2,6-dichlorobenzoic acid and 260 mg of cadmium sulfate 8 / 3 hydrate (CdSO4·8 / 3H2O) were added to a glass tube, 2.0 mL of a mixed solvent (composed of N,N-dimethylacetamide (DMA) and water in a volume ratio of 1:6.5) was added to the glass tube, the pH of the system was adjusted to 3.0 with nitric acid, the glass tube was sealed by melting, and then transferred to a constant temperature reaction box, reacted at 140°C for 10 h, and naturally cooled to room temperature after the reaction was completed. It was observed that light yellow needle-like crystals precipitated at the bottom of the glass tube, and the crystals were collected, vacuum dried, and weighed to obtain 3.5 mg, which was recorded as coordination polymer CP1 (hereinafter referred to as CP1). The yield was 54%.
[0048] The crystals obtained in this example were subjected to structural characterization and performance testing:
[0049] 1. H NMR spectrum analysis
[0050] The crystals prepared in this example were analyzed by nuclear magnetic resonance spectroscopy, and the spectrum was as follows: Figure 3 shown.
[0051] 2. Single crystal X-ray diffraction analysis
[0052] The crystals of appropriate size obtained in this example were selected and placed on a SuperNova X-ray single crystal diffractometer using graphite monochromatized Mo-Kα radiation. Single crystal test was performed. The main crystal data and correction parameters of the coordination polymer CP1 are shown in Table 1 below, and some bond length and bond angle data are shown in Table 2 below.
[0053] Table 1: Crystallographic data of coordination polymer CP1
[0054]
[0055]
[0056] Table 2: Some bond lengths of coordination polymer CP1 / and bond angle / ° data
[0057]
[0058]
[0059] The crystal structure of the obtained crystal at 298K was further determined. Figure 4 As shown. Figure 4 It can be seen that CP1 has a one-dimensional chain skeleton, and the Cd(II) pair connected by three auxiliary carboxylates and a water molecule acts as a template to guide the arrangement of functional ligands. Non-parallel arrangement of C=C bonds was observed in CP1, and the distance between the olefin bond centers was and Greater than The Schmidt criterion for solid-state [2+2] cycloaddition is not satisfied.
[0060] The XRD pattern of the cadmium coordination polymer was obtained by fitting the above crystallographic data. Figure 5 The crystal obtained in this embodiment was ground and then subjected to XRD detection, and the obtained XRD pattern was as shown in Figure 5 It can be seen that the powder X-ray diffraction curve of the product obtained in this example is completely consistent with the simulated curve calculated from the single crystal X-ray diffraction data, indicating the phase purity of the coordination polymer sample.
[0061] Therefore, the above analysis can determine that the crystal obtained in this example is the target product cadmium coordination polymer of the present invention.
[0062] 2. Thermogravimetric analysis
[0063] The coordination polymer CP1 obtained in this example was subjected to thermogravimetric analysis (TGA), and the results were as follows: Figure 6 As shown. Figure 6 It can be seen that the coordination polymer CP1 has good stability below 280°C in a nitrogen atmosphere, after which thermal decomposition occurs. CP1 has an obvious weight loss phenomenon at around 443K, which is mainly due to the removal of water molecules in the coordination solvent.
[0064] 3. Powder X-ray Diffraction Analysis
[0065] The coordination polymer CP1 obtained in this example is heated at about 443K (169.85°C) to remove the solvent water molecules. The XRD spectra before and after heating are as follows: Figure 7 As shown by Figure 7 It can be seen that the XRD spectra before and after heating show obvious structural changes, which verifies that the removal of coordinated water molecules after heating causes the structure of the coordination polymer CP1 to change.
[0066] 4. Infrared analysis
[0067] Infrared tests were performed on the untreated crystals of the coordination polymer CP1 in Example 1 and the crystals after phase transition after heating to 443K. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that the untreated crystals have a wavelength of 3000-3400 cm -1 There is a characteristic peak of water at 3000-3400cm -1 There is no characteristic peak of water at , indicating the loss of coordinated water. The CO stretching vibration peak of the carboxylic acid group (1380cm -1 and 1390cm -1 ) merged into one peak (1388cm -1 ), which indicates that the coordination environment of the carboxylic acid group has changed.
[0068] 5. Analysis of Light Response Behavior
[0069] The coordination polymer CP1 obtained in this example was irradiated with 365nm ultraviolet light at 298K, and it was found that it did not change after the irradiation. By heating the coordination polymer CP1 to 443K and irradiating it with 365nm ultraviolet light, obvious changes in appearance were observed, the crystals became opaque and darker in color, and light response behaviors such as bending and cracking appeared, such as Fig. 9The H NMR spectrum can confirm the occurrence of the [2+2] photocycloaddition reaction under 365nm UV irradiation before and after heating, with obvious cyclobutane peaks, such as Fig.10 As shown. Fig.10 It can be seen that the coordination polymer CP1 did not undergo a [2+2] photocycloaddition reaction when exposed to 365nm ultraviolet light at 298K, but after heating to change the structure, it underwent a [2+2] photocycloaddition reaction when exposed to 365nm ultraviolet light, and exhibited light response behaviors such as bending and cracking. More detailed illumination experiments have shown that the coordination polymer CP1 has obvious backlight bending behavior after being heated, such as Fig.11 As shown, as the irradiation time increases, the angle of the crystal backlight bending gradually increases. Therefore, the cadmium complex polymer of the present invention can be used in the field of photo-driven driving.
[0070] Comparative Example 1
[0071] Example 1 was repeated, except that in step 3), the same volume of N,N-dimethylformamide, diethylformamide or 1,4-dioxane was used instead of N,N-dimethylacetamide.
[0072] After the reaction was completed, the mixture was slowly cooled to room temperature, and no crystals were observed to be precipitated in the glass tube. Further concentration of the liquid obtained after the reaction was completed also did not result in any crystals being precipitated.
[0073] Comparative Example 2
[0074] Example 1 was repeated, except that in step 3), under the condition that the total volume of the mixed solvent remained unchanged, the volume ratio of N,N-dimethylacetamide and water in the mixed solvent was changed to 1:2.5, 1:4, 1:5, 1:6, 1:7.5, 1:8 or 1:9.
[0075] After the reaction was completed, the mixture was slowly cooled to room temperature, and no crystals were observed to be precipitated in the glass tube. Further concentration of the reaction solution obtained did not result in any crystal precipitation.
[0076] Example 2
[0077] Repeat Example 1, except:
[0078] In step 1), the amount of cuprous iodide added is 0.23 g.
[0079] In step 2), the amount of 4-vinylpyridine added is 1.45 g.
[0080] In step 3), the amount of cadmium sulfate 8 / 3 hydrate added is 258 mg, and the volume ratio of N,N-dimethylacetamide and water in the mixed solvent is changed to 1:6.7.
[0081] After the reaction was completed, the mixture was slowly cooled to room temperature, and pale yellow needle-like crystals were precipitated at the bottom of the glass tube. The yield was 63%.
[0082] The product obtained in this example was subjected to single crystal diffraction and other analyses, and it was determined that the obtained light yellow needle-shaped crystals were the cadmium complex polymer described in the present invention.
[0083] Example 3
[0084] Repeat Example 1, except:
[0085] In step 1), tetrakis(triphenylphosphine)palladium is used instead of bistriphenylphosphine palladium dichloride, cuprous chloride is used instead of cuprous iodide, and sodium carbonate is used instead of triethylamine.
[0086] In step 3), the volume ratio of N,N-dimethylacetamide to water in the mixed solvent is changed to 1:7.0.
[0087] After the reaction was completed, the mixture was slowly cooled to room temperature, and pale yellow needle-like crystals were precipitated at the bottom of the glass tube. The yield was 37%.
[0088] The product obtained in this example was subjected to single crystal diffraction and other analyses, and it was determined that the obtained light yellow needle-shaped crystals were the cadmium complex polymer described in the present invention.
[0089] Example 4
[0090] Repeat Example 1, except:
[0091] In step 2), 1,4-dioxane is used instead of N,N-dimethylformamide, and cesium carbonate is used instead of potassium carbonate.
[0092] In step 3), the pH of the system is adjusted to 4.0 with hydrochloric acid, and the reaction is carried out at 150° C. for 8 h.
[0093] After the reaction was completed, the mixture was slowly cooled to room temperature, and pale yellow needle-like crystals were precipitated at the bottom of the glass tube. The yield was 52%.
[0094] The product obtained in this example was subjected to single crystal diffraction and other analyses, and it was determined that the obtained light yellow needle-shaped crystals were the cadmium complex polymer described in the present invention.
[0095] Application Example 1: Preparation of composite membrane
[0096] The crystals of the coordination polymer CP1 prepared by the method described in Example 1 were heated to 443K and kept warm for 10 hours, and then ground into fine powder in an agate mortar (30 minutes). The powder was then mixed with a 10wt% PVA aqueous solution at a mass ratio of 1g:2mL and stirred to obtain a uniform viscous liquid, which was dripped into a Teflon substrate mold with a dry and clean surface, and dried in a constant temperature oven at 60°C. After the solvent was completely volatilized, it was peeled off from the Teflon substrate mold to obtain a composite membrane.
[0097] Application Example 2: Photoresponse Analysis of Composite Films
[0098] The composite film prepared in Example 1 was cut into rectangular pieces of 1 cm × 0.2 cm, and one end of the piece was fixed to one end of a paper sheet, and a 10 mg foam ball was fixed to the other end. The composite film was irradiated with 365 nm ultraviolet light from bottom to top, and the process was recorded with a camera. Fig.12 It was found that under 365nm ultraviolet light irradiation, the composite film quickly bends backlight and can easily lift a 10mg foam ball, which shows that the composite film is expected to be used in optical brakes, soft robots and other aspects.
[0099] Application Example 3: Photoresponse Analysis of Composite Films
[0100] The composite film prepared in Application Example 1 was cut into a bird shape, and the composite film was irradiated with 365 nm ultraviolet light from top to bottom, and the process was recorded with a camera, as shown in FIG. Fig.13 It was found that under 365nm ultraviolet light irradiation, the composite film quickly bends backlight, simulating the action of a bird spreading its wings, which indicates that the composite film is expected to be used in optical brakes, soft robots, bionics and other aspects.
[0101] Application Example 4: Photoresponse Analysis of Composite Films
[0102] The composite film prepared in Application Example 1 was cut into rectangular strips of 2 cm × 0.2 cm and laid flat on a table. The composite film was irradiated with 365 nm ultraviolet light from top to bottom, and the process was recorded with a camera. Fig.14 It was found that under 365nm ultraviolet light irradiation, the composite film quickly bends backlight into the shape of an arch bridge, which indicates that the composite film is expected to be used in optical brakes, soft robots, etc.
Claims
1. A cadmium coordination polymer that regulates light stimulus response behavior through thermal phase transition, which belongs to the monoclinic system, P21 / c space group, and the unit cell parameters are: α=90.00°, β=114.694(8)°, γ=90.00°.
2. The method for preparing the cadmium coordination polymer according to claim 1, characterized in that: The ligand represented by the following formula (I), cadmium sulfate and 2,6-dichlorobenzoic acid are placed in a reaction container, a mixed solvent is added, the system is adjusted to acidity, the reaction container is sealed and then placed under heating conditions for reaction, and the obtained product is obtained; wherein the mixed solvent is a composition composed of N,N-dimethylacetamide and water in a volume ratio of 1:6.5-7.0; 3. The preparation method according to claim 2, characterized in that: The cadmium sulfate is selected from one or a combination of two or more of anhydrous cadmium sulfate, cadmium sulfate hydrate and cadmium sulfate 8 / 3 hydrate.
4. The preparation method according to claim 2, characterized in that: Adjust the pH of the system to ≤5.
0.
5. The preparation method according to claim 2, characterized in that: The reaction is carried out at ≥100°C.
6. A composite film, characterized in that: The invention comprises a crystal obtained by heating the cadmium coordination polymer as claimed in claim 1 to above 150° C. to undergo a thermal phase transition.
7. The method for preparing the composite membrane according to claim 6, characterized in that: The cadmium coordination polymer of claim 1 is heated to above 150° C., the crystals undergoing phase change are ground and then evenly mixed with the substrate, the obtained viscous liquid is poured into a mold, dried, and peeled off to obtain the product.
8. The preparation method according to claim 7, characterized in that: The cadmium coordination polymer is heated to 150°C to 180°C and kept at this temperature for 2 to 12 hours to cause a phase change.
9. A photoactuator, characterized in that: Made from the composite membrane described in claim 6.
10. Use of the cadmium coordination polymer according to claim 1 or the composite film according to claim 6 in photoinduced driving.